2021
DOI: 10.1093/pubmed/fdab248
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-existing conditions and perceived health status on mental health during the COVID-19 pandemic

Abstract: Background Patients with pre-existing conditions and poor health status are vulnerable for adverse health sequalae during the COVID-19 pandemic. We investigated the association of pre-existing medical conditions and self-perceived health status with the risk of mental health complications during the COVID-19 pandemic. Methods In October—December, 2020, 1036 respondents completed online survey that included assessment of pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
5
25
1
1
Order By: Relevance
“…The association between mental illness and poor self-perceived health generally agrees with those obtained in previous studies ( 72 , 73 ). The fundamental link between mental health, physical health, and functional disability that has two pathways from one to the other may provide a conceptual framework.…”
Section: Discussionsupporting
confidence: 91%
“…The association between mental illness and poor self-perceived health generally agrees with those obtained in previous studies ( 72 , 73 ). The fundamental link between mental health, physical health, and functional disability that has two pathways from one to the other may provide a conceptual framework.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study corroborate previous research documenting an association between self-perceived health status and symptoms of depression, anxiety, and stress ( 55 ). Moreover, these results showed that chronic illnesses were not associated with symptoms of depression, anxiety, and stress ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 90%
“…It is a concerning finding that individuals with co-morbid medical conditions were more likely to increase their smoking given their higher risk of more severe COVID-19 illness [ 49 ]. One potential explanation for this association is that those with medical conditions might have felt more stress and/or experienced greater mental health complications because of their medical status, which, in turn, promoted smoking [ 25 , 50 , 51 ]. Another possibility is that having a medical co-morbidity may be related to greater difficulty quitting smoking.…”
Section: Discussionmentioning
confidence: 99%